(untitled) (Theatrum historiae, 2024)
The main aim of this paper is to discuss the role of Christian women in ritual murder accusations that took place in the Polish-Lithuanian Commonwealth from the 16th to the 18th centuries. Although the specificity of this issue might suggest that only the figures of Jewish women were considered, the reality was in fact quite different. In many cases, the deeds of Christian women were the most important element determining the course of events. Particular attention is given here to the various roles assigned to Christian women. They were perceived not only as accusers and defenders of the faith, but also as betrayers and accomplices to crimes. As such, it is necessary to consider their motives as well as the position and roles traditionally attributed to women in Christian culture. This study is based first and foremost on anti-Jewish booklets printed within the territory of the Polish-Lithuanian Commonwealth between 1546 and 1772, but also draws upon information from trial records relating to the cases of ritual murder accusations, which serve as complementary sources. The comparison of these two different sources makes it possible to arrive at a clearer picture of the past and to achieve a better understanding of the issues reshaped by the authors of the booklets. Because of that, anti-Jewish literature took the form of a specific kind of manipulation that used fear and anxiety to create a social reality that profoundly shaped attitudes towards Jews and women of the Christian faith.